The Education System in Post-conflict Syria – Examining PIRLS as an International Assessment Measure to Ensure the Quality of Students Achievements - Ibrahim, Yaser Abdulrahman (2023)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2022)